2015
DOI: 10.1891/0886-6708.vv-d-13-00137
|View full text |Cite
|
Sign up to set email alerts
|

Violent Death Rates and Risk for Released Prisoners in North Carolina

Abstract: Released prisoners face high risk of early mortality. The risk of violent death, specifically homicide and suicide, are addressed in this study. Data on inmates released from the North Carolina Division of Adult Corrections (N = 476) matched to the Violent Death Reporting System are analyzed to estimate rates and demographic and criminal justice-related predictors. Violent death rates for persons released from prison were more than 7 times higher than for the general adult population. Results from multinomial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 32 publications
2
20
1
Order By: Relevance
“…The overall mortality rate was lower in North Carolina during this same time period; however, we did not specifically examine sub-injury categories within unin- tentional injuries such as drug overdoses. For violent deaths, these findings dovetail with the work from Lize et al that found released inmates in North Carolina were more likely to experience a violent death than the general population [11]. Suicide and homicide were 14 times and 7 times greater than expected (respectively).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The overall mortality rate was lower in North Carolina during this same time period; however, we did not specifically examine sub-injury categories within unin- tentional injuries such as drug overdoses. For violent deaths, these findings dovetail with the work from Lize et al that found released inmates in North Carolina were more likely to experience a violent death than the general population [11]. Suicide and homicide were 14 times and 7 times greater than expected (respectively).…”
Section: Discussionsupporting
confidence: 77%
“…Suicides were associated with risk of reincarceration, relationship problems, depression, and other life circumstances [10]. Another study found that violent death rates among released prisoners were 7 times higher than the general population, and that the risk of being a homicide victim decreased with age and increased with being a male or a minority [11]. A decrease in suicide was associated with being a minority, release without probation or community corrections supervision, and receipt of substance abuse treatment in prison.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…All-cause mortality for prisoners after release from prison is higher than in the general population (Farrell and Marsden 2008 ) and the risk of suicide for released prisoners is high in the first month in the community (Pratt et al 2006 ). In both cases, having a diagnosed mental health condition confers additional risk (Lize et al 2015 ). Prisoners with severe mental illness may also have poor outcomes on forensic measures with higher rates of reoffending and return to prison, especially in those with co-occurring substance use disorders (Baillargeon et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%